ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN - Nurrofi, Akhmad (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2015)
This study aims to examine and analyze the influence of workdiscipline, supervision, and motivation to job satisfaction that impact onmorale. The data was collected through questionnaires distributed andimplemented to 79 employees working at PT.Carefast in Semarang. Thedata analysis in this study used SPSS version 17.The result of analysisshows that discipline, motivation, competency have positive effect onperformance variable.